2023
DOI: 10.21203/rs.3.rs-2703930/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The gut microbiota of tropical marine fish is largely uncultured and distinct from surrounding water microbiota

Abstract: Marine fishes along with their unique gut microbiotas are at threat of extinction. Studying the gut microbes of marine fishes is an important part of conservation. The gut microbiota of only a small fraction of the more than 32,000 known fish species has been investigated. In this study we analysed the gut microbiota composition of more than 50 different wild fish species from tropical waters. Our results show that the fish harbour gut microbiota that are distinct from that of the surrounding water and that lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Microbiota structures of the fin and kidney tissue from the present study were distinct from the structure of surrounding water microbiota, which was also the case for previous studies (67, 68). Although some bacteria derived from tissue overlapped with those of water microbiota, tissue microbiota often has specific bacterial consortia (20, 69). Bacteria composition analysis also revealed that temperature had a significant effect on diversity and taxonomic structure of the barramundi fin and kidney microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbiota structures of the fin and kidney tissue from the present study were distinct from the structure of surrounding water microbiota, which was also the case for previous studies (67, 68). Although some bacteria derived from tissue overlapped with those of water microbiota, tissue microbiota often has specific bacterial consortia (20, 69). Bacteria composition analysis also revealed that temperature had a significant effect on diversity and taxonomic structure of the barramundi fin and kidney microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…In salmon gut, exposure to high water temperature favored growth of Vibrio spp. (69, 70). In the current study, there was a lower abundance of pathogenic bacteria Vibrio and Tenacibaculum in healthy versus moribund fish after heat treatment.…”
Section: Discussionmentioning
confidence: 99%